Based on the relationship between anxiety of existential meaninglessness, hope level, and fear of progression, explored the effect of preoperative nursing with Orem theory in the senile cataract population - Zhang, Yanli; Cheng, Yanmiao; Liang, Yan; Shao, Mengfei; Chen, Aiai (Frontiers in Psychology, 2024)
Cataracts, characterized by a decrease in vision due to the clouding of the lens, can progress to blindness in advanced stages. The rising incidence of cataract cases has led to a significant number of patients experiencing negative emotions associated with vision loss, thereby diminishing their quality of life. In clinical practice, it is imperative for healthcare professionals to consider the psychological well-being of cataract patients. Currently, there is a scarcity of research focusing on psychological evaluations, such as assessing feelings of meaninglessness among individuals with cataracts.This study aims to investigate the factors influencing the anxiety of existential meaninglessness and to explore the relationships among existential anxiety, Herth hope index levels and fear of progression in the elderly cataract-affected population.Additionally, it evaluates the effectiveness of Orem's nursing care strategies.Utilizing a sociodemographic questionnaire, the Existential Meaninglessness Anxiety Scale (EM-A), Herth Hope Index Level Scale, and the Fear of Progression Questionnaire-Short Form (FoP-Q-SF), this research employed convenience sampling for a cross-sectional and intervention study. The retrospective study sample comprised 1,029 individuals, while the intervention study included 317. The intervention design assessed psychological changes in existential meaninglessness following Orem's preoperative nursing interventions. Multiple linear regression analysis was employed to ascertain the determinants of EM-A within the population of elderly patients with senile cataracts. Pearson correlation analysis elucidated the relationship between EM-A, levels of hope, and the FoP-Q-SF among this demographic. Subsequent investigations, utilizing a t-test, evaluated the effects by comparing the data before and after the implementation of the interventions.The correlation between EM-A, hope levels, and FoP-Q-SF was statistically significant (P < 0.05). Factors such as age, education level, alcohol consumption habits, hope levels, and FoP-Q-SF scores significantly affected EM-A scores (P < 0.05). Orem's nursing framework significantly reduced existential anxiety (P < 0.05).Among elderly patients with cataracts, existential anxiety was generally moderate.Hope levels and fear of progression were closely associated with the EM-A. The novel Orem preoperative care model effectively addresses clinical issues. In clinical practice, it is crucial to address psychological problems and enhance patients' quality of life.